A Preliminary Research to Develop A Customized Set of Vocabulary Size Test - Sumarni, Laurentia (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2014)
This is a preliminary research to investigate useful words to function effectively in academic contexts, vocabulary size, the first-year students word list, and the steps to design the customized set of entry-level vocabulary size test. This research was a library research. To find out the ELESP students current vocabulary size, a vocabulary size test designed by Paul Nation was administered. The results show that useful words were (1) high-frequency words containing 2,000 word families, (2) academic words specified in the Academic Word List (Coxhead:2000), (3) technical words, (4) low-frequency words. The result of the administration of Nations Vocabulary Size Test shows that the students scores range between 33 and 96 words, with the mean score of 66. It means that the students vocabulary size ranges between 3,300 and 9,600 word families. The average students vocabulary size was 6,600 word families, which imply that most ELESP students are ready to read texts containing 88.7% word coverage. In order to increase their vocabulary size by 10,000 or more, they need to learn technical words and low-frequency words of a specialized subject area. Using Nations specifications for making the test, some procedures of test design are: Sampling the words for the items, Making the Stem, Writing the choices, The Order of the items in the Test, Piloting, Administering the Test. The decisions on curriculum, materials and teaching strategies should be based on the results of vocabulary size to gain optimum learning outcome.